2021
DOI: 10.1002/ejp.1750
|View full text |Cite
|
Sign up to set email alerts
|

The association between exposure to domestic abuse in women and the development of syndromes indicating central nervous system sensitization: A retrospective cohort study using UK primary care records

Abstract: Background Domestic abuse is a global public health issue. The association between the development of central sensitivity syndromes (CSS) and previous exposure to domestic abuse has been poorly understood particularly within European populations. Methods A retrospective cohort study using the ‘The Health Improvement Network,’ (UK primary care medical records) between 1st January 1995–31st December 2018. 22,604 adult women exposed to domestic abuse were age matched to 44,671 unexposed women. The average age at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The current reality of war in Eastern Europe testifies to immeasurable misery, so it is intuitively understandable that this enormous stressor influences everything, including individual pain perception. Similarly, the assessed relationship problems might also encompass domestic abuse in the sense of controlling, coercive, threatening behavior, violence, or abuse in a relationship, likely causing tremendous distress and suffering [8,38]. In support of this reasoning, both war experiences and relationship problems in the sense of domestic abuse and violence have been shown to lead to a severe dysregulation of the HPA axis, being also evident in PTSD and being associated with higher pain sensitivity [15,39].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The current reality of war in Eastern Europe testifies to immeasurable misery, so it is intuitively understandable that this enormous stressor influences everything, including individual pain perception. Similarly, the assessed relationship problems might also encompass domestic abuse in the sense of controlling, coercive, threatening behavior, violence, or abuse in a relationship, likely causing tremendous distress and suffering [8,38]. In support of this reasoning, both war experiences and relationship problems in the sense of domestic abuse and violence have been shown to lead to a severe dysregulation of the HPA axis, being also evident in PTSD and being associated with higher pain sensitivity [15,39].…”
Section: Discussionmentioning
confidence: 97%
“…Central sensitization is defined as an increased responsiveness of nociceptive neurons to normal and subthreshold afferent input, due to a prolonged but reversible increase in excitability and synaptic efficacy of neurons in central nociceptive pathways, causing hypersensitivity and responsiveness to non-noxious stimuli [2][3][4][5]. It is assumed that repetitive or tonic nociceptive stimulation, as well as chronic negative emotions and distress, e.g., (childhood) trauma, neglect, and abuse, may be associated with hypothalamic-pituitary-adrenal (HPA) axis dysregulation and central sensitization [6][7][8]. As patients suffering from chronic pain disorders often show increased sensitivity to pain and pressure stimuli, assessing pain sensitivity serves as a central diagnostic characteristic in routine clinical assessment that supports treatment planning for patients with chronic pain [1].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the relative importance of adverse events in adult life per se, the available information in the existing literature is less obvious because most of the studies have combined childhood and adulthood abuse into lifetime abuse history. However, lifetime abuses are indeed associated with GI and somatic symptom severity (16,39,40). Our study only found an association between adult sexual abuse and GI and somatic symptom severity, whereas no associations were found with adult physical abuse.…”
Section: Discussionmentioning
confidence: 99%
“…For this study, we have used Read codes to define the exposure (domestic abuse) and outcome of interest (periodontal disease; see AppendixA). The dataset and these code lists have been previously used to explore the life course of those experiencing domestic abuse and those experiencing oral disease ( Chandan et al., 2021 ; Chandan et al., 2021 ; Chandan et al., 2020 ; Chandan et al., 2019 ; Chandan et al., 2020 ; Chandan et al., 2019 ; Zemedikun et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%